Cantovivência and its artistic manifestations - Gonçalves Villanova, Victoria Cristina (2021)
The article aims at the beginning of a consolidation of the cantovivência concept and the development of its uses. It is a word created during monographic writing and which has been cited as a possibility of representation and configuration of what is the interpretation of a black life, in this case having as analysis the interpretation of songs, which at times can be called protest songs. The objective is to demonstrate a constant and secular struggle that racialized people fight against white, heteronormative, racist and sexist supremacy. This struggle is represented by their black, afrodis-poric, resistant and artistic bodies. The living and singing of black and brown lives are political.